Preskripsi Antibiotika Pada Anak: Tinjauan Tentang Dosis Dan bentuk Sediaannya - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1994)
Dosage pattern of antibiotics for children and their availability forms prescribed by physicians were studied. The objectives of this study were to investigate the systematic antibiotic dosage and their availability forms prescribed by doctors for children under 12 years old and the problems that may raised. The investigation was conducted using 484 samples selected randomly on five pharmacies in Yogyakarta in December 1931. The results indicated that the antibiotics widely used were co4rimoxazol (37.3%), amoxycillin (221%), ampicillin (17.4%), and erythromycin (11.3%). The dosage range of those antibiotics given to the each of age group was large. The wide range of dosage might be due to the differences on the references and method of dosage calculation for children. The methods mostly used by the doctors were the standard dosage from USP,DI (1990) and were based on the ideal (minimum) body weight. The results also showed that about 18.4% of the samples were lower than the standard prescription and 44.7% of them was ampicillin. Almost ampicillln was given In syrup form and was lower than recommended standard dosage. The study also found that the availability form mostly prescribed by the doctors was pulveres. It is necessarely to study further the effect of the variety and the wide range of dosage of antibiotics prescribed by doctors for children and their solution in order to achieve the optimal benefit of clinics without resulting negative effects on children.